The riddle of the Rajah's ruby - Blyton, Enid. (b, 2013)
When Nick and Katie's friends, Sophie and David, inherit a mysterious cursed ruby it causes all sorts of trouble for them. It's up to Nick and Katie to rescue them. Their explorations take them to a hidden house and beautiful temple but will the children escape from the clutches of Sophie and David's captors before it's too late?
Keywords: Mystery fiction; Adventure stories; Children's stories